Watfa, Ägypten. Oase Fayum. Die Arbeiten des Jahres 2016 - Römer, Cornelia (e-Forschungsberichte des DAI, 2017)
Philoteris (the modern name is Watfa) was founded under Ptolemy II in the 3rd century BC, and abandoned in the 4th century AD. A geomagnetic plan of the site in the north-western Fayum Oasis, produced by T. Herbich and his team in 2011–2014, shows water ways and canals around and within the village to allow for a thorough understanding of the water supply of the inhabitants of the village, and the gardens and fields around. An impressive building outside the settlement and well connected to the water canals attracted attention; it turned out to be the only archaeologically attested Gymnasium in Egypt so far. The 2016 campaign focussed on that building and its connection to the water network around.